Comparison of shrinkage deformations in resin mortars modified with different waste materials - Bernardeta Dębska; Guilherme Jorge Brigolini Silva; Marina Altoé Caetano; Bruna Silva Almada (Budownictwo o Zoptymalizowanym Potencjale Energetycznym)
Resin-based mortars are characterized by excellent strength parameters, together with very good chemical resistance and a short time to achieve installation and serviceability. However, a limitation of their use may be their relatively high curing shrinkage. This parameter can be improved by modifying the composition of mortars with, among other things, recycled materials. This article describes and compares the results of tests on four types of epoxy mor-tars: a control sample (unmodified) and three modified samples with waste polyethylene ter-ephthalate glycolysate, each one containing additional waste polyethylene or rubber from car tires. A positive effect on the mechanical strength of the mortars was demonstrated thanks to the modification. The shrinkage of the mortars was monitored from the time of formation. The partial substitution of aggregate by rubber granules or polyethylene agglomerate reduced the shrinkage value of the mortars based on a glycolysate-modified matrix by 14.2 % and 7.1 %, respectively.